(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of the main methodological and theoretical levels of the modern Russian historiography of the „soviet every day history” in 20-th – 30-th of the XX century. On the basis of the analysis of the monographic literature, dissertational works and scientific articles the author allocates characteristic conceptual components of the given direction of a historical science.